1993
DOI: 10.1183/09031936.93.06030440
|View full text |Cite
|
Sign up to set email alerts
|

Protection by N-acetylcysteine against pulmonary endothelial cell damage induced by oxidant injury

Abstract: The protective effect of N-acetylcysteine (NAC) against oxidant lung injury was investigated in a model of acute immunological alveolitis in the rat. Intrapulmonary immune complex deposition into rat lungs, induced by intratracheal infusion of immunoglobulin G (IgG) anti-bovine serum albumin (BSA) antibodies and intravenous injection of the antigen, caused lung damage associated with a marked decrease in [14C]5-hydroxytryptamine ([14C]5HT) uptake capacity, taken as a biochemical marker of endothelial cell func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…NAC is a glutathione precursor that is commonly used as an antidote for acetaminophen overdose. In addition to augmenting glutathione synthesis, NAC has oxygen radical scavenging properties, 43 and NAC therapy has been examined in several clinical studies of ARDS patients with modest but encouraging results. In one trial of 66 patients with ARDS, NAC therapy was associated with a small increase in lung compliance compared with the control group but did not affect the survival rate.…”
Section: Potential Therapies For Alcohol-associated Lung Injurymentioning
confidence: 99%
“…NAC is a glutathione precursor that is commonly used as an antidote for acetaminophen overdose. In addition to augmenting glutathione synthesis, NAC has oxygen radical scavenging properties, 43 and NAC therapy has been examined in several clinical studies of ARDS patients with modest but encouraging results. In one trial of 66 patients with ARDS, NAC therapy was associated with a small increase in lung compliance compared with the control group but did not affect the survival rate.…”
Section: Potential Therapies For Alcohol-associated Lung Injurymentioning
confidence: 99%
“…A deficiency in the activity of endothelial NOS may be responsible for pulmonary hypertension. It has been suggested that ROS may initiate pulmonary hypertension during ascites as vascular endothelial cells are the primary targets of oxidant injury (Sala et al, 1993). ROS deactivates NO and inhibits the activity of NOS (Rengasamy and Johns, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the journal, SALA et al [25] rep01t on the protective effect of NAC against oxidant lung injury induced by intrapulmonary immune complex deposition in rats. Serotonin uptake in the perfused lung served as a biochemical marker for pulmonary endothelial ceU function.…”
Section: K L Maier*mentioning
confidence: 99%